SIMULATION STUDY ON SMART SPRINKLER FOR UNIFORMITY IMPROVEMENT - Ab. Kadir, Nuraqliah (IRC, 2016)
The irrigation system is needed for agricultural and landscaping field. From the literature review showed the original model of sprinkler cannot distribute water thoroughly to the targeted area then; we come with the new invention of sprinkler which is, Smart Sprinkler. The target for this project is to improve the water distribution of Smart Sprinkler by using Ansys simulation. In order to achieve the result, author will validate the baseline sprinkler with smart sprinkler in Ansys simulation by controlling the water flow out by different types of nozzles. The result showed that Smart Sprinkler can supply twice volume of water compared to baseline sprinkler. Then, Smart Sprinkler can supply 17.05 cm³ and for Baseline Sprinkler, it is 13.57 cm³ volume of water could be supplied to the targeted area. As a conclusion, Smart Sprinkler can distribute more volume of water to the system to meet the sufficient needed for the system.